CHARACTERIZATION OF THE BURNING REGIME OF THE TERRA RONCA STATE PARK, GOIÁS - Conceição, Igor Barbosa da; Aguiar, Lívia Lima Leite; Martins, Patrick Thomaz de Aquino (Geosaberes; Vol 15 (2024), 2024)
Although it brings together most of the burned areas in Brazil, the Cerrado still lacks detailed information about the fire regime in some localities in its territory. Aiming to contribute to meeting this demand, this study aimed to characterize, for the period between 1984 and 2020, the burning regime in the Terra Ronca State Park (PETeR), located in the state of Goiás. From the interpretation of Landsat satellite images, fire scars were identified in all the years analyzed. Neither large fire was observed nor a clear relationship with the Park's creation, demarcation or land tenure history. Regarding frequency, two regions were discriminated, both presenting low recurrence of burning. The regime identified in the PETeR suggests the maintenance of vegetation in the Park and, thus, the fulfillment of the basic objective of this category of UC.